Rational approaches for optimizing chemical functionality of plasma polymers: A case study with ethyl trimethylacetate. Issue 3 (7th December 2020) - Saboohi, Solmaz; Coad, Bryan R.; Short, Robert D.; Michelmore, Andrew; Griesser, Hans J.
Abstract: Improved retention of desirable chemical structures during plasma polymerization requires rational tailoring of plasma‐phase conditions. Using ethyl trimethylacetate, we studied the effects of pressure and power on the contribution of intact molecular ions to deposition and retention of ester groups. The abundance of protonated molecular ions in plasmas varies with pressure and power, but the functionality of plasma polymers, assessed by X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass spectrometry, is not correlated. Together with high ion flux, the ion energy distribution was found to be a key parameter and needs to be tailored to enable the soft landing of ions on the surface after traversing the sheath. The compromise between the abundance of ions and their energy distribution is optimal near the transition between the α and γ plasma phases. Abstract : This study investigates rational optimization of the contribution of molecular ions to the formation of plasma polymers, to incorporate desired chemical groups into films. The data show that a high concentration of heavy ions is not sufficient for generating films with high amounts of ester groups; these ions must remain intact while traversing through the sheet, after which they soft‐land on the surface, which requires control of the ion energy distribution.